Digital Technology-Based Assistance for De Jenangs MSME in Malang City - Fajar Dio Wahyu Tri Amukti; Naja Jessyka Maulani Putri; Agung Winarno; Agus Hermawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the challenges faced by UMKM De Jenangs in enhancing competitiveness amid the development of the traditional culinary sector and increasing demands for digitalization. This research aims to strengthen managerial capacity, optimize digital marketing, reinforce visual identity, and digitize operational and financial systems through assistance based on the UMKM Digitalization Strategy (SDIGI). The method employed is an individual approach conducted over nine weeks through observation, interviews, HPPT analysis, development of visual media, optimization of social media, website development, and the implementation of digital bookkeeping. The results indicate an improvement in order management efficiency, financial transparency, branding quality, and marketing reach through the utilization of social media, local influencers, and the official website. In conclusion, the assistance provided has had a significant impact on business professionalization and the strengthening of the digital identity of the UMKM. The proposed recommendations include the need for regular monitoring of website management and financial journals, continuous improvement of digital content quality, and further training to enable the UMKM to adapt optimally to shifts in consumer behavior and the dynamics of the digital market.